The influence of 2, 4-dichlorophenoxyacetic acid concentration and light condition via rice callus induction varieties MR219, MR220 and MR297 / Muhammad Faiz Rosli - Rosli, Muhammad Faiz (Faculty of Plantation and Agrotechnology, 2019)
The Malaysian population rely heavily on the rice as their staple food for daily consumption. Currently, Malaysia has about 71.4% rice self-sufficiency level (SSL). Tissue culture of Malaysian rice is important in improving tissue culture protocol. Objectives of the study were to study the effect of different 2, 4-D hormone concentrations and culture condition towards rice (Oryza Sativa L.) variety via callus induction and plant regeneration. In this study, three varieties of rice were selected which are MR219, MR220 and MR297 with different 2, 4-D concentrations (1.5mg/L, 2.0mg/L and 2.5mg/L). The seeds were cultured in 16/8 h photoperiod and completely dark condition. Three replications were done and the results were taken after four weeks. The average percentage for callus induction, roots and shoots initiation were calculated. Among these three samples, MR220 exhibited the highest frequency (66.67%) of callus induction in 16/8 h photoperiod at 2.5mg/L 2, 4-D and MR219 showed highest frequency (66.67%) for completely dark condition at 2.5mg/L 2, 4-D. Overall results indicated that the best callus frequency (66.67%) was induced when supplemented with 2.5mg/L 2, 4-D in 16/8 h photoperiod for variety MR220.